Evaluasi Model CIPP CADET Training Program di SMA Progresif Bumi Shalawat - Arisatul Ainiyah; Karwanto Karwanto; Mustaji Mustaji; Amrozi Khamidi; Muhammad Nur Salim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to obtain a clear picture of the problems studied in this case, which is the purpose of this study, namely to determine the results of the evaluation of the Context, Input, Process and Product of the Cadet Training Program at SMA Progresif Bumi Shalawat. Evaluation research refers to